EVALUASI KINERJA SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG SPMB DI MI MASLAKUL HUDA LAMONGAN: STUDI LITERATURE REVIEW - Ariny Tamamul Minnah (Jurnal Manajemen Pendidikan, 2025)
MI Maslakul Huda Lamongan as a private Islamic elementary school faces similar crucial issues, where the SPMB process is still semi-manual despite efforts to integrate the Ministry of Religion's SIM, resulting in data delays and a lack of transparency for parents of prospective students. The Management Information System (MIS) plays a crucial role in supporting the New Student Admission Selection (SPMB) process in madrasah ibtidaiyah through data transparency, administrative efficiency, and accurate document verification, yet it faces challenges such as low digital literacy among human resources and limited infrastructure in private MI in East Java like Maslakul Huda Lamongan. This study applies Systematic Literature Review (SLR) using PRISMA protocol on 45 articles from 2020-2025 sourced from Google Scholar and SINTA to identify performance evaluation gaps of MIS. Findings show that SIMPATIKA and EMIS effectively reduce manual errors in SPMB, but major gaps include the scarcity of comparative private-public studies and holistic rural infrastructure evaluations. Recommendations encompass continuous HR training, local platform integration, and waterfall model for contextual MIS optimization.